KEADAAN KAHAR (OVERMACHT) DALAM PERJANJIAN JUAL BELI ONLINE - Taufiq Rizki (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Technological developments in modern times encourage people to use the internet in buying and selling transactions where sellers and buyers are only connected via internet media and delivery (levering) of goods is carried out by relying on third party services. The implementation of this online buying and selling agreement raises many new questions, such as what constitutes a valid requirement for an online buying and selling agreement, what is the legal relationship that is formed between the parties in online buying and selling and the impact that occurs on online buying and selling in the event of a default due to force majeure (overmacht).